Послуги: облік та формування собівартості - Голуб, Наталя Олександрівна; Holub, Nataliia (Науково-виробничий журнал «Бізнес-навігатор», 2024)
UA: У статті проаналізовано дискусійні питання щодо обліку собівартості робіт, послуг. Торгівля послугами є важливою частиною світогосподарських зв’язків. Розглянуто економічне визначення поняття «послуги». Послуги становлять собою діяльність однієї особи на користь іншої особи. Цілеспрямована діяльність, результати якої мають прояв у корисному ефекті. З’ясовано які сфери мають послуги та складові виробничої собівартості. Визначено, що сфера послуг включає велику групу галузей, важливою рисою діяльності яких є створення специфічного товару з відповідними особливостями. Визначено необхідність використання калькуляційного рахунку по формування виробничої собівартості, загальновиробничого рахунку та рахунку собівартості реалізації послуг. Розглянуто нормативну базу, щодо формування виробничої собівартості наданих послуг. Національні стандарти визначають порядок обліку витрат однаково для всієї продукції – як для товарів, так і для робіт або послуг. І для собівартості робіт і послуг залишаються ті самі підходи. /// EN: The article analyzes debatable issues regarding cost accounting of works and services. The main problems are identified. Trade in services is an important part of global economic relations. The fundamental difference between products and services is that services are consumed at the time of provision. Income – based on the degree of completion of the operation, if the results can be reliably estimated. So expenses are simultaneously with such income. The economic definition of the concept of "service" is considered. Services are activities of one person for the benefit of another person. Purposeful activity, the results of which are manifested in a useful effect. The concept of a service is more multifaceted than the concept of a product. Service is a wide range of various types of activities. It has been clarified which areas have services and components of the production cost. It was determined that the sphere of services includes a large group of industries, an important feature of whose activity is the creation of a specific product with appropriate features. The necessity of using the calculation account for the formation of the production cost, the general production account and the account of the cost of the implementation of services was determined. It is necessary to form a production cost for services. The principle of assigning costs and forming the cost price is the same for both products and works and services. The regulatory framework regarding the formation of the production cost of the provided services is considered. National standards determine the procedure for accounting costs in the same way for all products – both for goods and for works or services. And the same approaches remain for the cost of works and services. Business transactions must be recorded in the reporting period in which they arose according to the primary documents. That is, not by the date of drawing up the primary document, but by the date and period of the transaction. The list of production costs, objects for calculating the cost price must be written in the accounting policy as clearly and clearly as possible, without double interpretations. It is important to clearly state in the accounting policy how and for which services you will calculate the cost price. The accounting policy must correspond to the actual real accounting.
Services: accounting and cost formation
Keywords: послуги; роботи; собівартість; витрати; калькуляція; services; works; cost price; costs; calculation